2020
DOI: 10.1136/bjsports-2020-102967
|View full text |Cite
|
Sign up to set email alerts
|

What is the risk of recurrent concussion in children and adolescents aged 5–18 years? A systematic review and meta-analysis

Abstract: ObjectiveWe aimed to examine the risk of concussion in children with a previous history of concussion.DesignSystematic review and meta-analysis. The primary outcome was number of children with and without a previous lifetime history of concussion who sustained a diagnosed concussion within each study period. Risk of bias was assessed using the Newcastle-Ottawa Scale. A random effects model was used to estimate a pooled risk ratio (RR) with corresponding 95% CIs; results were summarised in forest plots.Data sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…Because the risk of subsequent concussions may be high 55 and may increase the risk of mental health issues, we conducted a sensitivity analysis to assess whether number of concussions occurring after the index concussion would affect the main results. We introduced a time-dependent variable representing concussions during the follow-up period; any emergency or primary care practitioner visit resulting in a concussion diagnosis at 4 weeks or more after the index event for cohort entry was defined as a new concussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the risk of subsequent concussions may be high 55 and may increase the risk of mental health issues, we conducted a sensitivity analysis to assess whether number of concussions occurring after the index concussion would affect the main results. We introduced a time-dependent variable representing concussions during the follow-up period; any emergency or primary care practitioner visit resulting in a concussion diagnosis at 4 weeks or more after the index event for cohort entry was defined as a new concussion.…”
Section: Discussionmentioning
confidence: 99%
“…Youth who have incurred a concussion are at 3 times higher risk of sustaining a subsequent concussion. 55 Multiple concussions may increase the likelihood of MHPs. However, even when concussions after the index concussion were taken into account, mental health disorders, psychiatric hospitalization, and self-harm remained significantly associated with concussion, and the magnitude of risk of developing one of these outcomes did not change.…”
Section: Discussionmentioning
confidence: 99%
“…However, growing evidence suggests that psychosocial factors are an important predictor of recurrent injury and determinant of return to preinjury level of performance among athletes with orthopedic injuries. 3 , 4 , 5 , 6 , 7 , 8 , 9 Athletes with a previous history of concussion are nearly 4 times more likely to sustain a recurrent concussion than those without, 10 yet clinicians have received little guidance on how to measure or mitigate the impact of psychosocial factors on RTS medical clearance following a concussion despite the known existence of psychosocial sequelae. 11 …”
Section: Introductionmentioning
confidence: 99%
“… 7 , 16 , 17 , 18 Injury-related biases in this area limit generalizability, 19 and a concussion-specific understanding of psychosocial factors associated with RTS is critical due to key differences in recovery from concussion compared with orthopedic injuries including the fact that: (a) objective diagnostic and recovery biomarkers are lacking for concussion; (b) symptoms are multidimensional with wide-ranging functional impacts; (c) prognosis and recovery trajectories are unclear; (d) treatment options are poorly understood; (e) few concussion studies use clearly defined RTS criteria despite recommendations for a multimodal evaluation; 2 , 20 and (f) RTS before recovery is complete is a risk factor for recurrent concussion with possible serious consequences, including death. 10 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…A few potential risk factors for pediatric sport-related concussion have been identified. Systematic reviews have identified strong evidence that history of a previous concussion is a risk factor for sustaining a future concussion (8,9), with previously concussed youth athletes having more than 3 times greater risk of sustaining a future concussion (pooled risk ratio = 3.64; 95% CI: 2.68-4.96) (8). In addition, several retrospective studies of youth athletes report that boys have a greater lifetime history of concussion than girls (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%